2005
DOI: 10.4319/lo.2005.50.2.0629
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the fluid mud layer in Lake Apopka, Florida

Abstract: Since it switched from a macrophyte-dominated state to a turbid, algal-dominated state in 1947, Lake Apopka has developed a layer of flocculent sediments with characteristics of fluid mud covering most of the lakebed and averaging 47 cm in thickness in 1996. Waves in this large, shallow lake frequently resuspend the upper portion of the fluid mud and frustrate programs designed to decrease the trophic state. We tested two hypotheses for its origin, one that the fluid mud layer represents the buildup of organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…It cannot be assumed that once OBs have settled to the bottom they will remain stationary, since floc is easily disturbed. For example, water entering from the bottom can cause sediment to move upwards in lakes,57, 58 and wind and rain will resuspend unconsolidated sediment in shallow water bodies 59–61. Once resuspended in the water column, OBs attached to sediment particles/flocculent material could move off site through such processes as downstream transport and overland flow during flooding.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be assumed that once OBs have settled to the bottom they will remain stationary, since floc is easily disturbed. For example, water entering from the bottom can cause sediment to move upwards in lakes,57, 58 and wind and rain will resuspend unconsolidated sediment in shallow water bodies 59–61. Once resuspended in the water column, OBs attached to sediment particles/flocculent material could move off site through such processes as downstream transport and overland flow during flooding.…”
Section: Discussionmentioning
confidence: 99%
“…Some nutrient-enriched shallow lakes also have alternative states [47]: a clear state with macrophytes and turbid state with phytoplankton. A major disruption of submerged vegetation due to a hurricane, a drought, or a period of increased water depth could transform a lake to a turbid phytoplankton-dominated state and it may be very difficult for it to return to a clear-water plant-dominated state [48].…”
Section: Discussionmentioning
confidence: 99%
“…The lake switched and became a dark water lake and has only slowly recovered its transparency. Lake Apopka, Florida was by a variety of indicators a clear-water lake with vast coverage of SAV until 1946, when a hurricane tore up the SAV and pushed the lake into a phytoplankton-dominated condition that persists today [48]. What sets Lake Apopka apart from Okeechobee are two factors: (1) Okeechobee sediments contain a large percentage of inorganic solids that result in extreme light-limitation when they are suspended into the water column, preventing CyanoHABs from occurring or persisting; and (2) available information suggests that, in Apopka, all of the SAV was torn up and pulverized into particulate organic C and nutrients that fueled algal growth lake-wide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Duin et al (1992) observed a small oxidized layer on top of the soft mud layer, indicating that both layers were (to some extent) present in 1991-1992. Various earlier modeling studies on the TSM in Lake Markermeer (Vlag 1992) and numerous studies on other shallow lakes such as Lake Okeechobee (e.g., Ji 2004, Jin andSun 2007), Lake Apopka (Bachmann et al 1999(Bachmann et al , 2005, and Lake Taihu (Hu et al 2006) mentioned comparable mobile muddy layers and vertical gradients in suspended matter concentrations near the bottom during windy situations. To our knowledge, however, this was never before directly linked to effects on freshwater bivalves; therefore, ours is the first study to experimentally test this.…”
Section: Discussionmentioning
confidence: 95%